Effect of TiO2-Al2O3nanoparticle mixing ratio on the thermal conductivity, rheological properties, and dynamic viscosity of water-based hybrid nanofluid - Wanatasanapan V.V.; Abdullah M.Z.; Gunnasegaran P. (Elsevier Editora Ltda, 2023)
Alumina; Aluminum oxide; Crystallite size; Deionized water; Mixing; Nanoparticles; Oxide minerals; Rheology; Testing; Thermal conductivity; TiO2 nanoparticles; Titanium dioxide; Viscosity; Correlation modeling; Different proportions; Dynamic viscosities; Experimental test; Mixture compositions; Nano-particle mixing; Rheological property; Volume concentration; Nanofluidics